PENGARUH GREEN EDUCATION DALAM MENINGKATKAN JIWA GREEN ENTREPREUNERSHIP PADA SISWA SEKOLAH DASAR - Sabila Putri Permana; Desty Farizka; Tin Rustini (JS (JURNAL SEKOLAH), 2023)
Abstract: The Effect of Green Education in Enhancing the Spirit of Green Entrepreneurship in Elementary School Students. This study aims to instill a green entrepreneurship spirit in elementary school students. The character of green entrepreneurship in students can be developed through green education. This study used the library study method by collecting data sourced from journals related to the topic of discussion, then data analysis was carried out using descriptive qualitative analysis through literature study. The results obtained from this study are the characteristics of green entrepreneurship that must be possessed by elementary school students, namely self-confidence, optimism, curiosity, innovative, creative, caring for the environment, daring to take risks, hard work, and having rational actions. Green entrepreneurship needs to be integrated with green education in activities such as integration into subjects, extracurricular activities, self-development activities in schools, teaching materials, school culture, and local content. There is a strategy in the transformation towards green entrepreneurship, namely creating or producing green products, changing consumer behavior towards green products, and marketing green products. The strategy for developing a green entrepreneurship spirit in elementary school students can be through modeling, observation, field trips, and market days. Keywords: Green Economy, Green Entrepreunership, Green Education Abstrak: Pengaruh Green Education dalam Meningkatkan Jiwa Green Entrepreunership pada Siswa Sekolah Dasar. Penelitian ini bertujuan untuk menanamkan jiwa green entrepreneurship pada siswa Sekolah Dasar. Karakter green entrepreneurship pada siswa dapat ditumbuhkembangkan melalui green education. Penelitian ini menggunakan metode studi kepustakaan dengan mengumpulkan data yang bersumber dari jurnal terkait topik bahasan, kemudian dilakukan analisis data menggunakan analisis kualitatif deskriptif melalui studi pustaka. Terdapat hasil yang diperoleh dari penelitian ini yaitu karakter-karakter green entrepreneurship yang harus dimiliki seperti percaya diri, optimis, rasa ingin tahu, inovatif, kreatif, peduli lingkungan, berani mengambil resiko, kerja keras, dan memiliki tindakan yang rasional, karakter-karakter tersebut harus dimiliki oleh siswa pada Sekolah Dasar. Sehingga, green entrepreneurship perlu diintegrasikan dengan green education terhadap kegiatan-kegiatan seperti pengintegrasian ke dalam mata pelajaran, kegiatan ekstrakurikuler, kegiatan pengembangan diri di sekolah, bahan ajar, kultur sekolah, dan muatan lokal. Terdapat strategi dalam transformasi menuju green entrepreneurship yaitu menciptakan atau menghasilkan green product, mengubah perilaku konsumen menuju green product, dan memasarkan green product. Adapun strategi untuk menumbuhkembangkan jiwa green entrepreneurship pada siswa Sekolah Dasar dapat melalui modelling, observasi, karya wisata, dan market day. Kata Kunci: Green Economy, Green Entrepreunership, Green Education